Determinants on Green Repurchase Intention Vegan Skincare Products: The Mediation of Attitude Towards Behavior - Ramadhina, Aini Leily; Paramita, V. Santi (Ilomata International Journal of Management, 2024)
This research aims to examine determinants on green repurchase intention, mediated by attitude towards behavior in vegan skincare products from The Body Shop. The data analysis technique used is descriptive test, multiple regression using SPSS version 25 and sobel test. The number of respondents involved in this reasearch were 271 samples dominated by women from 842 thousand population instagram followers @thebodyshop. Data collection techniques using random sampling which is included in the probability sampling. Of the seven proposed research hypotheses supported by empirical data. The finding of study indicate that attitude towards behavior mediates the effect of green knowledge and green perceived value on repurchase intention. The results of this study are also expected to be useful for managing the assessed object related to the design of a strategy or program that is relevant to improving the quality of the attributes.